Evaluation of the Antimicrobial Resistance Pattern of Nosocomial Infections in Patients Hospitalized in Chamran Heart Educational, Medical, and Research Center of Isfahan - Mehrnoush Dianatkhah; Zeinab Sadat Davoodi; Rasool Soltani; Fatemeh Shafiee; Alireza Hosseini (Journal of Research in Pharmacy Practice)
Objective: According to the importance of evaluating the antimicrobial resistance pattern in the management of nosocomial infections (NIs), we decided to investigate the prevalence of antimicrobial resistance in Chamran Heart Hospital. Methods: This retrospective cross-sectional observational study was performed for 6 months from February to July 2022 at Shahid Chamran Hospital of Isfahan, Iran. All hospitalized patients with any NIs were eligible for the study. Clinical specimens were obtained from patients with NIs. All specimens underwent microbial culture, and if bacterial growth developed, differential tests were performed. Antibiotic susceptibility testing also was performed per the standards of Clinical and Laboratory Standards Institute, 2022. Findings: Out of 201 examined samples, urinary infection (34.83%), pneumonia (27.86%), and sepsis (13.43%) were reported to be the most prevalent infections. Among Gram-negatives (76.12%), Citrobacter spp. (26.37%), Escherichia coli (24.87%), and Klebsiella spp. (11.44%) were the most common pathogens. About 54.9% of Citrobacter spp., 33.3% of E. coli, and 45.45% of Klebsiella spp. were resistant to carbapenems. About 1.88% and 15% of Citrobacter spp. were identified as pan-drug-resistant bacteria and extensively drug-resistant (XDR), respectively. In addition, 4.34% of Klebsiella spp. were identified as XDR. Among Gram-positives (23.88%), Enterococcus spp. (8.95%) was identified as the most common pathogen, and the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE) was 11.11% and 61.11%, respectively. Conclusion: In our study, carbapenem-resistant Enterobacteriaceae accounts for about 50% of all NIs. Moreover, despite the low prevalence of MRSA, VRE was reported to be high in our center when compared with other studies.